Seasonal Anomalies in Stock Returns: Evidence from India - Kaur, Manpreet (Indian Journal of Finance, 2011)
The present study is an endeavour to investigate seasonal anomalies, if any, existing in stock returns in India. The daily closing prices of two indices- BSE 500 and S&P CNX 500 have been used to examine the presence of month-of-the-year and day-of-the-week effects in the Indian stock market. The reference period ranges from January 2002 to December 2009. The findings show presence of month-of-the-year effect but absence of day-of-the-week effect in Indian stock market. This indicates that the Indian stock market is not fully efficient yet. Its implication is that the existence of month-of-the-year effect may provide opportunities to formulate profitable trading strategies so as to earn the increased return that does not commensurate with the risk.